Comparison of the efficacy and safety of norethisterone vs. combined oral contraceptive pills for the management of puberty menorrhagia - Patel, Nita K.; Patel, Shalin; Damor, Rohit; Pandya, Manish R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The most common cause of puberty menorrhagia is immaturity of the hypothalamic pituitary ovarian axis. Treatment is directed towards stabilizing the endometrium and treating the hormonal alterations. The objective of this study was to compare the efficacy and safety of norethisterone and combined oral contraceptive (COC) pills for the management of puberty menorrhagia. Methods: A total of 60 young girls from age of menarche to 19 years with menorrhagia were randomized to receive either norethisterone or COC pills. The end points included change from baseline in health-related quality-of-life parameters, estimation of blood loss and effect on hemoglobin level. Health-related quality-of-life question scores at baseline and after treatment were calculated as mean for norethisterone group and COC pills group. Results: Norethisterone and COC pills treatment groups showed mean improvement in Menorrhagia Impact Questionnaire (MIQ) scores compared to baseline. However, the total mean score was higher in norethisterone group compared to COC pills group after three treatment cycles (21 Vs 17). The treatment failure was less in norethisterone group compared to COC pills group. Conclusions: Use of norethisterone was more effective and better tolerated compared to combined oral contraceptive pills for the management of puberty menorrhagia.